The Lost Flavors of Indian Palate: A Review - Chef Chandrakant Divakar (AG Volumes, 2021)
Spicy delights abound in Indian cuisine. Ingredients and processing techniques are the primary determinants of a food’s ultimate profile. Authentic Indian cuisine requires a wide range of spices to get the right taste profile. Ethnic cuisine’s quality is influenced by regional and ethnic customs as well as subjective variables like the chef’s competence and cooking technique. Home-cooked meals were preferred by the vast majority of Indian customers. In contrast to that, contemporary eating out culture is quickly altering Indian society’s attitude. Several fast-food chains already have a presence in India, thanks to the country’s fast-paced culture, hectic schedules, competitive nature, rising numbers of working women, and the nuclear family idea, among other factors. India’s fast-food industry is exploding due to favourable demographics, shifting customer preferences, and increasing disposable income. India, on the other hand, is losing its unique culinary tastes. Literature reviews have examined food choice factors. The paper’s topic matter includes the growth and developments in the fast food industry, which provide the groundwork for rising consumption and the ensuing societal problem of health degradation due to rising global obesity.